A case for international neurosurgical experience: US resident experiences with pediatric spinal dysraphism cases. (October 2014) - Rocque, Brandon G.; Lam, Sandi
<x content-type="archive" xml:space="preserve">Abstract</x> Introduction: In the National Resident Report of Neurological Surgery Case Logs prepared by the department of Applications and Data Analysis of the Accreditation Council for Graduate Medical Education (ACGME), the Resident Review Committee for Neurological Surgery conducted a survey of the total experience of residents completing programs in 2008–2011. Methods: Review of case numbers from the Resident Review Committee survey and at an East African hospital with visiting US neurosurgical trainees was conducted. Results: US residents reported their experiences with the ACGME index cases categorized as 'dysraphism — pediatric cases'. The national resident average of pediatric spinal dysraphism cases totaled for all years was 8·1 cases with a standard deviation of 11. In contrast, more than four spinal dysraphism cases per week were reported per resident during a rotation at Kijabe Hospital in Kenya (mean duration of rotation: 2·4 weeks). The majority of these cases were myelomeningocele cases. The pediatric neurosurgeon in residence at Kijabe has logged over 300 spinal dysraphism cases per year since summer of 2010. Conclusion: A 4-week international resident rotation could potentially provide experience with an average of four spinal dysraphism cases per week. Over one month, this could eclipse the 90th percentile of US resident experience for an entire residency. This is borne out by individual experiences of residents who have visited Kijabe, Kenya, over the past several years. The role and value of international neurosurgical experiences for residency training can be significant, especially for treatment pathologies rarely encountered in many areas of the USA.